2006
DOI: 10.1103/physrevlett.97.156104
|View full text |Cite
|
Sign up to set email alerts
|

Slippage of Water Past Superhydrophobic Carbon Nanotube Forests in Microchannels

Abstract: We present in this letter an experimental characterization of liquid flow slippage over superhydrophobic surfaces made of carbon nanotube forests, incorporated in microchannels. We make use of a µ-PIV (Particule Image Velocimetry) technique to achieve the submicrometric resolution on the flow profile necessary for accurate measurement of the surface hydrodynamic properties. We demonstrate boundary slippage on the Cassie superhydrophobic state, associated with slip lengths of a few microns, while a vanishing sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
353
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(373 citation statements)
references
References 21 publications
13
353
0
1
Order By: Relevance
“…Whereas the slip and viscous drag reduction have been extensively characterized in continuous flows by, for example, nanorheological measurements 22 and particle image velocimetry 23 , considerably less is known about the friction and dissipation in discrete droplets. This can be considered to originate from the contemporary characterization methods, such as the optical contact angle goniometry, that measure static or quasistatic properties of the interfaces and contact angles 24 .…”
mentioning
confidence: 99%
“…Whereas the slip and viscous drag reduction have been extensively characterized in continuous flows by, for example, nanorheological measurements 22 and particle image velocimetry 23 , considerably less is known about the friction and dissipation in discrete droplets. This can be considered to originate from the contemporary characterization methods, such as the optical contact angle goniometry, that measure static or quasistatic properties of the interfaces and contact angles 24 .…”
mentioning
confidence: 99%
“…Due to the lower dynamic viscosity of air compared to water the trapped air layer on a superhydrophobic surface has a lubricating effect on the flow over it. Drag reducing properties of superhydrophobic surfaces have been observed experimentally in microfluidic devices (Choi, Westin & Breuer 2003;Ou, Perot & Rothstein 2004;Ou & Rothstein 2005;Joseph et al 2006;Daniello, Waterhouse & Rothstein 2009;Govardhan et al 2009;Tsai et al 2009;Rothstein 2010) and for coated objects, such as hydrofoils (Gotge et al 2005), settling spheres (McHale et al 2009) and cylinders (Muralidhar et al 2011), covering flow regimes from laminar to turbulent. In a stable configuration, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…using µ-PIV measurements (Ou & Rothstein 2005;Joseph et al 2006;Truesdell et al 2006;Tsai et al 2009), the slip length at the wall can be computed using relation (3.9) based on the wall velocity The diamonds show the optimum gas layer thickness/maximum drag reduction, whereas the circles and squares indicate the gas layer thicknesses needed to achieve 90 and 50 % of the maximum drag reduction.…”
Section: Slip Length Based On Velocity Profilementioning
confidence: 99%
“…Regular arrays of chemical patches [4,5,6] and posts [7,8,9,10] of different shapes and sizes are regularly fabricated and several authors [11,12,13] have even shown the possibilities of manufacturing multi-scale surface patterns. Recently such patterning has been used to control the movement of drops [16,17] and to attempt to enhance flow in microchannels [18,19].…”
Section: Introductionmentioning
confidence: 99%